Participatory action research in the field of neonatal intensive care: developing an intervention to meet the fathers' needs. A case study - Betty Noergaard; Helle Johannessen; Jesper Fenger-Gron; Poul-Erik Kofoed; Jette Ammentorp (SAGE Publishing, 2016)
Background: In neonatal intensive care units (NICUs) health care professionals typically give most of their attention to the infants and the mothers while many fathers feel uncertain and have an unmet need for support and guidance. This paper describes and discusses participatory action research (PAR) as a method to improve NICUs' service for fathers. Our goal is to develop a father-friendly NICU where both the needs of fathers and mothers are met using an approach based on PAR that involves fathers, mothers, interdisciplinary healthcare professionals, and managers. Design and methods: This PAR process was carried out from August 2011 to July 2013 and included participant observations, semi-structured interviews, multi sequential interviews, workshops, focus groups, group discussion, and a seminar. The theoretical framework of validity described by Herr and Anderson's three criteria; process-, democratic-, and catalytic validity were used to discuss this PAR. Results: Twelve fathers, 11 mothers, 48 health professionals and managers participated in the PAR process. The collaboration ensured the engagement for viable and constructive local changes to be used in designing the concept of the father friendly NICU. Conclusions: This paper contributed new knowledge of how PAR can be used to ensure that participants engaged in the field are involved in the entire process; consequently, this will ensure that the changes are feasible and sustainable.